Motivational aspects of development of strategic network partnership in the agro-industrial complex - Vаlentyna Stadnyk; Galyna Krasovska; Pavlo Izhevskiy; Tetiana Tomalia; Lilia Khomych; Pavlo Matveev (Agricultural and Resource Economics, 2021)
Purpose. The purpose of this paper was to determine motivational factors of structural changes in the agro-industrial sector of Ukraine, which will strengthen the ability of business entities to generate larger added value flows and increase efficiency through the development of strategic network partnerships. Methodology / approach. While writing the article the following methods were used: methods of economic and statistical analysis – to study the dynamic of indicators that reflect the results of sectoral structural changes of the enterprises’ activities in the sector of agriculture, forestry and fisheries of Ukraine during 2016–2019; critical analysis – to identify shortcomings in the legislative field of Ukraine, which deform motivational vectors, negatively affect the development of agro-industrial complex; morphological analysis and synthesis – to prove the feasibility of interpreting the term “network capital” in a narrow and broad sense; scientific abstraction and graphic visualization – to build the model of formation of network capital and use in the processes of organizational interaction of participants in a strategic business partnership; mathematical modelling – to formalize the conditions under which the network partnership participants will avoid manipulation by the expert environment in the apportionment of the costs and revenues from the implementation of business projects. Results. It has been studied the dynamic of indicators that reflect the results of the sectoral and structural changes in activities of Ukrainian enterprises in the agriculture, forestry, and fisheries sector during 2016–2019. It has been highlighted shortcomings in the legislative field of Ukraine, which distort the vectors of motivational influence on the development of agro-industrial complex, causing the corruption schemes spread in the decisions and actions of economic agents. The essential content of the term “network capital” in a narrow and broad interpretation has been differentiated and the motivational basis for its increase by the business network participants has been highlighted. The processes of formation and use of network capital in the inter-organizational interaction of participants of strategic business partnership have been modelled. Nash equilibrium theory has been applied to increase the reliability of the position assessment of business network participants in the total costs and revenues apportionment and it has been proved that this forms the motivational basis for long-term cooperation. Originality / scientific novelty. The author’s interpretation of the term “network capital” in a broad and narrow sense with emphasis on motivational aspects of this capital increasing in the agro-industrial business network has been proposed. The model of network capital formation and use in the processes of organizational interaction of participants in a strategic business partnership has been constructed. There have been modelled the conditions under which the participants of the network partnership will avoid manipulation by the expert environment in the apportionment processes of costs and revenues from the business projects implementation, which will improve their motivation to cooperate. Practical value / implications. The main results of the study can be used for (i) elimination of some gaps in the institutional environment of Ukraine, which distort the motivational vectors of agricultural development; (ii) managing growth processes of network capital to increase the aggregate ability of business network participants to create new consumer value with high added value; (iii) improving the motivational basis for long-term cooperation of business network participants by increasing the reliability of their positions assessment in the total costs and revenues apportionment.